implementasi model pembelajaran picture and picture terhadap siswa kelas VIII materi bangun ruang sisi datar - teguh setiawan; Risdiana Chandra Dhewy; Eka Nurmala Sari Agustina (JEDMA Jurnal Edukasi Matematika, 2021)
Implementation is a way of activity which is planned orderly, carefully and specifically to gain the effective and efficient result which is reviewed from the teacher’s activity, students’ activity, study’s result and students’ responses in order to make the students actively act in the process of learning and the students will not confuse with many formulas found in the material of build space flat side, thus can implemented picture and picture model learning where this learning metode, the student must be active to use the picture and to be matched or sorted to be systematic sequence, such as arrange the picture orderly, appoint the picture, give information about the picture and explain the picture. This research was a descriptive quantitative research, the data gained from the research population sample which analyzed coincide with the statistic metode which was used then interpreted. Because of this research intended to know the implementation of learning mode of picture and picture in the VIII grade in Bilingual Terpadu Junior High School in the material of build space of flat side. In the implementation learning mode of picture and picture in this research, the score of teacher’s actixxity showed that 3,08 in the “good” category, in the part students’ activity from 12 indicator gained 8 very active and 4 active. In the part score of learning result classically gained 62,5%, this showed that classically can be said “incompleted” and from the students’ responses was positive stated because the response questionnaire in the “good” category.